The Influence of Causal Factors on Package Tour Repurchase Intention via Agoda Application of Consumers in Bangkok and Its Vicinity - Faksang, Krissada; Lekcharoen, Somchai (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The objective of this research was to 1) study the causal factors influencing consumers repurchase intention for package tour on Agoda Application in Bangkok and its vicinity and to 2) develop and to validate the consistency of a causal relationship modal of consumers repurchase intention for package tour on Agoda Application. The tools used in the research was online questionnaires. The sample group consisted of 215 people who have been repurchase package tour on Agoda Application and who have lived in Bangkok and its vicinity. The statistics used in data analysis were frequency, percentage. The structural equation model is used to analyze causal relationships to find the path to the causal influence. The result of the research showed that the causal relationship model was developed of 4 components were 1) perceived service quality 2) perceived value 3) satisfaction and 4) repurchase intention and accordance with empirical data consisting. The final was predictive coefficient of 0.80, indicating that the variables in the model can explain the variance of the consumers repurchase intention for package tour on Agoda Application by 80 percent. This research found that the satisfaction services were the most influence on direct effect consumers repurchase intention and the perceived service quality were the most influence on indirect effect consumers repurchase intention for package tour on Agoda Application in Bangkok and its vicinity.